Implikasi Hukum Pemisahan Pemilu Nasional dan Pilkada dalam Sistem Ketatanegaraan Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 135/PUU-XXII/2024 - Rana Syndri Dynanti; Punta Yoga Astoni (Decisio: Jurnal Ilmiah Hukum, 2026)
Constitutional Court Decision Number 135/PUU-XXII/2024 transformed the constitutional design by separating National and Local Elections to prevent systemic dysfunctions observed in previous simultaneous cycles. While this separation aims to enhance meaningful voting and local checks and balances, the recommended gap of two to two-and-a-half years introduces new sociopolitical risks. This study analyzes the implications of such separation based on the principles of democracy, government effectiveness, and legal certainty through normative legal research. The analysis reveals that the proposed timeframe is sub-ideal as it disrupts the proportionality of local elite circulation and triggers bureaucratic fragmentation due to the prolonged appointment of acting regional heads. Furthermore, the open legal policy regarding election scheduling remains vulnerable to partisan interests if not properly regulated. Therefore, this study recommends limiting the election gap to a maximum of one year to ensure stability in leadership transitions. Legal certainty must be strengthened by enacting regulations well in advance of the election year and ensuring fulfillment of meaningful participation standards. Such measures are crucial to guarantee that the open legal policy remains grounded in the substance of popular sovereignty and aligns with national development agendas.